2018
DOI: 10.1140/epjc/s10052-018-6038-z
|View full text |Cite
|
Sign up to set email alerts
|

The origin of multi-TeV flares from the nearest blazar Markarian 421

Abstract: Markarian 421 is a high-peaked BL Lac object and it has undergone many strong outbursts since its discovery as a TeV source in 1992. Markarian 421 has been studied intensively and was observed by various Cherenkov telescope arrays ever since. The outbursts of April 2004 observed by the Whipple telescope and of February 2010 by the HESS telescopes are explained well in this work by using the photohadronic model. To account for the attenuation of these highenergy gamma-rays by the extragalactic background light … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
(101 reference statements)
1
6
0
1
Order By: Relevance
“…However, the mean free path λ γγ for 12.2 GeV photon interacting with γ ≥1.4 MeV seed photon is λ γγ > R f if the photon density is n γ,f 10 10 cm −3 . This density is also consistent with the moderate efficiency of ∆-resonance process (Sahu et al 2018b), hence, attenuation in γ-rays in the inner jet due to e + e − production is negligible. It is worth mentioning here that, to fit the observed VHE spectrum of TXS 0506+056, it is not necessary to know the detail of the seed photon density, only the value of δ is enough to fit it.…”
Section: Vhe γ-Rays From Txs 0506+056supporting
confidence: 85%
See 1 more Smart Citation
“…However, the mean free path λ γγ for 12.2 GeV photon interacting with γ ≥1.4 MeV seed photon is λ γγ > R f if the photon density is n γ,f 10 10 cm −3 . This density is also consistent with the moderate efficiency of ∆-resonance process (Sahu et al 2018b), hence, attenuation in γ-rays in the inner jet due to e + e − production is negligible. It is worth mentioning here that, to fit the observed VHE spectrum of TXS 0506+056, it is not necessary to know the detail of the seed photon density, only the value of δ is enough to fit it.…”
Section: Vhe γ-Rays From Txs 0506+056supporting
confidence: 85%
“…where δ = α + β and F 0 is the normalization constant determined from the observed VHE SED. During the flaring period, the background seed photon flux behaves as a power-law Φ ∝ E −β γ where 0 < β ≤ 1.0 (Sahu et al 2018a). Recently, the flaring of HSP blazars have been classified into roughly three categories depending on the value of δ (Sahu et al 2019a).…”
Section: Photohadronic Modelmentioning
confidence: 99%
“…Again, during a 6-month long multi-instrument campaign (Banerjee et al 2019), a large VHE flare about 16 times larger than the usual one, was observed by MAGIC telescopes on 25th of April 2014 and soon it was followed-up by XMM-Newton and VERITAS. Several of the above multi-TeV flaring events from Mrk 421 have been explained extremely well by the standard photohadronic scenario (Sahu et al 2016(Sahu et al , 2018(Sahu et al , 2019.…”
Section: Flaring Of Mrk 421mentioning
confidence: 88%
“…There is also PKS B1424-418, a Flat Spectrum Radio Quasar that was in temporal and positional coincidence with a high-energy starting event (HESE) on 2012 December, a cascade-like event with a reconstructed energy of 2 PeV but a median positional uncertainty of ∼16 • that gives an estimated ∼ 5% chance of coincidence (Kadler et al 2016). In addition, there are several studies searching for gamma-ray counterparts and predicting consistent limits within the IC neutrino flux so far (Krauß et al 2014(Krauß et al , 2015Brown, Adams & Chadwick 2015;Glüsenkamp 2016;Padovani et al 2016); the successful SED modelling of blazars during flaring episodes using hadronic models (Mücke & Protheroe 2001;Diltz, Böttcher & Fossati 2015;Diltz & Böttcher 2016;Sahu, de León & Miranda 2017;Sahu, de León & Nagataki 2018a;Sahu et al 2018b); and hadronic emission has been proposed as an explanation for the spectral hardening in TeV energy gamma-ray spectra, behaviour which has been observed in some blazars [e.g. W Comae, 3C 66A (Böttcher et al 2013), 1ES 0229+200 (Tavecchio et al 2009), 1ES 1101-232 and H 2356-309 (Aharonian et al 2006)].…”
mentioning
confidence: 99%